Are Different Forms of Repetitive Negative Thinking Associated With Interpretation Bias in Generalized Anxiety Disorder and Depression?. (September 2019) - Krahé, Charlotte; Whyte, Jessica; Bridge, Livia; Loizou, Sofia; Hirsch, Colette R.
Worry and rumination, two forms of repetitive negative thinking (RNT), are prevalent in generalized anxiety disorder (GAD) and depression. Cognitive processing biases, especially the tendency to draw negative conclusions from ambiguous information (interpretation bias), may maintain worry and rumination. Yet the relationship between interpretation bias and both forms of RNT has not been explored in clinical versus nonclinical samples. In this cross-sectional study, participants with GAD ( n = 72), depression ( n = 79), or neither disorder ( n = 71) completed two tasks assessing interpretation bias, measures of worry and rumination, and reported negative thought intrusions during a behavioral task. Interpretation bias was associated with higher levels of worry, rumination, and negative thought intrusions. Both clinical groups generated significantly more negative interpretations than healthy comparison participants. These findings link interpretation bias to worry and rumination and establish the need for research investigating the causal role of interpretation bias in maintaining RNT.